The presence of a chromosomal abnormality in cytopenia without dysplasia identifies a category of high‐risk clonal cytopenia of unknown significance. Issue 3 (30th November 2022) - Brett, Victor‐Emmanuel; Lechevalier, Nicolas; Trimoreau, Franck; Dussiau, Charles; Dimicoli‐Salazar, Sophie; Coster, Lucie; Luquet, Isabelle; Nadal, Nathalie; Ribourtout, Bénédicte; Chapiro, Elise; Lefebvre, Christine; Tondeur, Sylvie; et al.
Abstract: Myelodysplastic syndromes (MDS) are hematological malignancies classically defined by the presence of cytopenia(s) and dysmorphic myeloid cells. It is now known that MDS can be preceded by a pre‐malignant condition called clonal cytopenia of unknown significance (CCUS), which associates a clonality marker with cytopenia in the absence of criteria of dysplasia. However, to date, it is not clear whether chromosomal abnormalities should be considered in the definition of CCUS or if they carry a prognostic impact in CCUS patients. In this study, we analyzed the clinico‐biological features and outcomes of 34 patients who presented with one or more cytopenias, an absence of significant dysplasia, and a presence of a chromosomal abnormality (CA). We named this entity chromosomal abnormality with cytopenia of undetermined significance (CACtUS). We show that these patients are slightly older than MDS patients and that they more frequently presented with normocytic anemia. Most CACtUS patients exhibited only one unbalanced CA. The number and type of mutations were comparable between CACtUS patients and MDS patients. Regardless of the cytogenetic abnormality, the clinicobiological characteristics, overall survival, and risk of progression to high‐risk (HR) MDS were similar between CACtUS patients and low‐risk MDS patients. Thus, we suggest that CACtUS patients can be considered as HR‐CCUS and should receive the follow‐up regimen recommended for MDS patients.